A view of ancient aroma culture through Museum-collected aroma utensils - Hong Qin (Wolters Kluwer Health/LWW, 2018)
Aroma fumigation is one of the traditional Chinese fumigating therapies. Moreover, the aroma culture is a combination of traditional Chinese medicine culture with Confucian and folk cultures. As historical marks, medical relics such as aroma utensils, herbs, and books can reflect the development and prosperity of aroma culture in history.